A study on the possible renovation of UPAC fast food center - Cacnio, Socorro Luz R.; Mayo Adelaida V. (1991.)
(no abstract provided by the author)
Thesis (BID)--University of the Philippines Diliman.
Keywords: UPAC Fast Food Center; Buildings -- Repair and reconstruction